The influence of flood frequency and duration on microcrustacean egg bank composition in dryland river floodplain sediments. (24th May 2021) - Chaki, Nipa; Reid, Michael; Nielsen, Daryl L.
Abstract: Several studies of temporary floodplain wetlands suggest that flood history is important to microcrustacean egg bank composition and hatching responses. However, these studies have largely focussed on contrasts among less frequently flooded areas (areas flooded every year to areas flooded once every 10–20 years) and less is known about variation at the more frequently flooded end of the gradient (from multiple floods per year to once every 2 years). Similarly, the effects of flood duration on egg banks have not been examined in detail. Thus, this study examines spatial variation in microcrustacean hatching at higher flood frequencies and in relation to inundation duration. Surface sediment samples were collected from dry anabranches of the Macintyre River floodplain in Australia during February 2018, with a range of flood frequency from approximately four times per year to one in 2 years. Anabranches were selected randomly from predefined flood frequency classes and clustered into three different flood history groups based on flood history variables. Soil samples were collected from deep and shallow locations within anabranches, with depth assumed to be a proxy for the duration of inundation. Sediment samples were inundated in mesocosms and hatched microcrustaceans sampled over 6 weeks. Microcrustacean abundance and assemblage composition varied by sites, relative depth, and duration of inundation. There was no variation by flood history groups. Highest numbers hatched from the deeper areas of anabranches, which is assumed to reflect differences in the egg banks of deep and shallow areas due to the longer duration of inundation in deeper areas. Duration also influenced hatching response from the egg bank, with more microcrustaceans hatching per unit time in the first 2 and final 2 weeks of the 6‐week trial than the middle 2 weeks. Species richness also varied by relative depth and duration of inundation with more taxa hatching from the deeper areas of anabranches. The study highlights the critical influence of flood duration on hatching patterns of microcrustaceans from inundated sediments. Therefore, changes to flood duration have the potential to influence microcrustacean assemblages and thus further changes to trophic interactions in temporary floodplain wetlands. ​